Direct Cervicoplasty - Jordan, J. Randall; Yellin, Seth (Facial Plastic Surgery, 2014)
Rejuvenation of the aging neck is one of the common reasons for the patients presented to facial plastic surgeons. In the author's opinion, most of these patients will be best served by a full rhytidectomy approach with periauricular incisions, skin flap undermining, and platysmaplasty. There is a subset of patients, however, who presented with complaints limited to the so-called Turkey Gobbler deformity, and who do not wish to undergo a full rhytidectomy approach. These patients may be well served by a lesser procedure such as a direct cervicoplasty or submentoplasty. The advantages of this approach include shorter operative time, faster recovery, and lower complication rates. The primary disadvantage of these more limited approaches is that there is an anterior cervical scar that may be visible under some conditions. This article will review the multiple options for skin incisions as well as details of the technique that the authors have found may lead to a successful rejuvenation of the submental region.
Keywords: cervicoplasty; submentoplasty; rhytidectomy; platysmaplasty